Rubber for tire transition layer as well as preparation method and application of rubber
By using natural rubber and modified epoxidized natural rubber in the tire transition layer and adding ingredients such as white carbon black and zinc methacrylate, the problem of low bonding strength between the airtight layer and the transition layer is solved, and the structural stability and safety of the tire are improved.
Patent Information
- Application Number
- CN202510882136.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-06-27
AI Technical Summary
In all-steel radial truck tires, the bonding strength between the airtight layer and the transition layer is low, leading to delamination problems and affecting the safety and service life of the tire.
Natural rubber and modified epoxidized natural rubber are used as the matrix materials, and ingredients such as white carbon black, silane coupling agent, and zinc methacrylate are added. A transition layer is formed through a mixing process to enhance the interface cross-linking and adhesion properties.
Significantly improve the adhesion between the transition layer and the airtight layer, improve the structural stability of the tire, and enhance the overall performance and safety reliability.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber materials, and in particular relates to a rubber for a tire transition layer, a manufacturing method and an application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.
[0003] All-steel radial truck tires offer advantages such as high load-bearing capacity and excellent wear resistance, and are widely used in the transportation industry. In the structure of an all-steel radial truck tire, the innerliner prevents compressed gas leakage. The carcass cord, located outside the innerliner, serves as the tire's load-bearing framework, maintaining internal tire pressure and transmitting supporting loads. The innerliner and carcass cord are connected by a transition layer. In the later stages of tire use, delamination between the innerliner and carcass cord can occur. Due to the complex stress states generated during vehicle operation, such as rolling deformation stress, road impact stress, and centrifugal force, coupled with reduced adhesion between the innerliner and carcass cord and inconsistent stress and strain, the innerliner can easily stretch and rupture at the delamination site. This can then cause gas blowby to separate the steel wire from the rubber of the carcass cord, ultimately leading to a blowout or tire damage, seriously threatening driving safety.
[0004] In existing technology, the innerliner often uses bromobutyl rubber as the rubber phase, leveraging its high polarity and high saturation to prevent gas permeation and ensure tire airtightness. The transition layer, on the other hand, often adopts a design similar to the tire tire tire rubber formula, leveraging the non-polarity and low saturation of natural rubber to provide better flexibility and processability. The structural differences between the natural rubber in the transition layer and the bromobutyl rubber in the innerliner are significant, resulting in weak intermolecular forces and poor compatibility between the two, making it difficult to form a good bonding interface. Regarding the vulcanization system, the innerliner often uses oxides or resin vulcanizers, while the transition layer uses sulfur vulcanization. Due to the different crosslinking reaction mechanisms, a tight, uniform crosslink network cannot be formed at the interface, resulting in low interfacial crosslink density and low bond strength, which leads to poor stress transfer between the two layers under load. Currently, the addition of tackifiers to improve adhesion is not ideal and may negatively impact other tire properties such as heat resistance, aging resistance, and elasticity, failing to fundamentally resolve the problem of poor adhesion between the transition layer and the innerliner. Summary of the Invention
[0005] In response to the deficiencies in the prior art, the present invention provides a rubber for a tire transition layer, a production method, and an application. Natural rubber and modified epoxidized natural rubber are used as the rubber matrix materials of the transition layer formula, and zinc methacrylate is added to enhance the interface crosslinking and adhesion between the transition layer and the airtight layer. The amount of white carbon black added is increased and a silane coupling agent is used to balance the bonding performance and processing performance. The obtained rubber product can not only ensure good bonding performance with the tire body, but also significantly improve the bonding force with the airtight layer, has long-lasting strong adhesion, can effectively solve the delamination problem, and improve the overall performance and safety reliability of the tire.
[0006] In order to achieve the above object, the technical solution of the present invention is: In a first aspect, a rubber for a tire transition layer comprises the following components in parts by mass: 50-90 parts of natural rubber, 50-10 parts of epoxidized natural rubber, 13.5-18 parts of carbon black, 31.5-42 parts of white carbon black, 3.15-4.2 parts of a silane coupling agent, 5-10 parts of zinc oxide, 1.5-3.5 parts of an antioxidant, 0.3-1.2 parts of cobalt boroacylate, 0.5-1.5 parts of stearic acid, 0.5-2 parts of resorcinol, 2-10 parts of zinc methacrylate, 3-5 parts of an adhesive, 4.5-6 parts of insoluble sulfur, and 1.3-2.5 parts of an accelerator; wherein the sum of the natural rubber and epoxidized natural rubber components is equal to 100 parts, and the mass ratio of white carbon black to carbon black is (6-8):(2-4).
[0007] In a second aspect, a method for preparing the rubber for the tire transition layer comprises the following steps: S1. Mix natural rubber and epoxidized natural rubber, knead at 135-165°C to obtain a rubber section M1, and cool; S2, mixing the first stage rubber M1, white carbon black, carbon black, silane coupling agent, zinc oxide, antioxidant and stearic acid, kneading at 142-158°C to obtain the second stage rubber M2, and cooling; S3, mixing the second stage rubber M2, cobalt boroacylate and resorcinol, kneading at 135-145°C to obtain the third stage rubber M3, and cooling; S4, mixing the three-stage glue M3 and the adhesive, kneading at 105-115°C to obtain the four-stage glue M4, and cooling; S5. Mix the fourth-stage rubber M4, zinc methacrylate, insoluble sulfur and an accelerator, and knead them at 95-105° C. to obtain the rubber for the tire transition layer.
[0008] In a third aspect, the application of the above-mentioned rubber for the tire transition layer includes: being used to bond the airtight layer and the carcass cord layer.
[0009] Optionally, the airtight layer comprises brominated butyl rubber, and the carcass ply comprises natural rubber.
[0010] The beneficial effects of the present invention are: In terms of the material system, the present invention uses natural rubber and modified epoxidized natural rubber as the matrix. The former gives the transition layer good flexibility and cushioning properties, while the latter enhances compatibility with the airtight layer and the vulcanization cross-linking effect by increasing polarity. Using white carbon black and carbon black as formula reinforcement materials, and adding a coupling agent at a dosage of about 10wt% of white carbon black, it can not only adjust the surface energy and enhance the cohesive strength, but also improve the filler dispersion and rubber bonding, achieving a balance between bonding performance and processing performance. The polymerization enhancement, coordination and interfacial effects of zinc methacrylate and epoxy natural rubber strengthen the cross-linking adhesion between the transition layer and the airtight layer; and can jointly enhance the cross-linking density and physical properties with epoxy natural rubber during the rubber vulcanization process. The new transition layer formula thus formed can significantly improve the bonding force and viscosity durability between the layers, optimize the structural stability of the tire, effectively solve the delamination problem, and comprehensively improve the performance and safety reliability of the tire. DETAILED DESCRIPTION
[0011] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs.
[0012] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof.
[0013] One or more embodiments of the present invention provide a rubber for a tire transition layer, comprising the following components in parts by mass: 50-90 parts of natural rubber, 50-10 parts of epoxidized natural rubber, 13.5-18 parts of carbon black, 31.5-42 parts of white carbon black, 3.15-4.2 parts of a silane coupling agent, 5-10 parts of zinc oxide, 1.5-3.5 parts of an antioxidant, 0.3-1.2 parts of cobalt boroacylate, 0.5-1.5 parts of stearic acid, 0.5-2 parts of resorcinol, 2-10 parts of zinc methacrylate, 3-5 parts of an adhesive, 4.5-6 parts of insoluble sulfur, and 1.3-2.5 parts of an accelerator; wherein the sum of the natural rubber and epoxidized natural rubber components is equal to 100 parts, and the mass ratio of white carbon black to carbon black is (6-8):(2-4).
[0014] Among the above ingredients, by systematically optimizing the material selection and component ratio of the transition layer formula, key contradictions such as poor interface compatibility caused by differences in rubber molecular structure and insufficient interface cross-linking density caused by incompatibility of vulcanization systems were resolved, thus overcoming the technical difficulties of delamination between the airtight layer, transition layer and carcass.
[0015] Optionally, the natural rubber is of STR20 grade and has an acetone extract content of 1.5 to 3.2 wt%. Natural rubber has excellent comprehensive properties, giving the transition layer good flexibility, high elasticity and processing adaptability, and can effectively buffer the stress of the tire during driving.
[0016] Optionally, the epoxidized natural rubber has an epoxidation degree of 10% to 20%, and the optional models include: one or two of ENR10 and ENR20; preferably, ENR10 with an epoxidation degree of 10%; the modified epoxidized natural rubber introduces epoxy groups to increase the polarity of the rubber, improve the compatibility with the brominated butyl rubber in the airtight layer, and enhance the adhesion between the transition layer and the airtight layer. The high chemical activity of the epoxidized natural rubber also helps to optimize the vulcanization cross-linking network, and can synergize with the airtight layer vulcanization system to form additional cross-linking points at the interface, construct a denser cross-linking network, significantly enhance the adhesion between the transition layer and the airtight layer, and improve the structural stability of the tire.
[0017] Optionally, the specific surface area of the white carbon black is 165±15m 2 / g; Silica has a higher specific surface area and stronger surface activity than carbon black. It can not only adjust the surface energy of the transition layer to promote close adhesion with the airtight layer, but also react with epoxidized natural rubber to enhance the cohesive strength of the transition layer.
[0018] Optionally, the carbon black is selected from one or more of N326, N375 and N330.
[0019] Optionally, the silane coupling agent is selected from one or both of bis-(3-(triethoxysilane)propyl)tetrasulfide (abbreviated as Si-69) and bis-(3-(triethoxysilane)propyl)disulfide (abbreviated as Si-75); The reaction between silane coupling agent and silica is relatively complex. Its sulfane group undergoes cross-linking reaction with the rubber molecular chain to form a stable chemical bond. In addition, the triethoxysilane group reacts with the hydroxyl group on the surface of silica to enhance the interfacial bonding between the filler and the rubber matrix. This dual effect improves the mechanical properties of the rubber, reduces hysteresis loss, and enhances the overall performance of the material.
[0020] Optionally, the zinc oxide has a specific surface area of 8.0±1.0m 2 / g, used in rubber to react with fatty acids to form zinc soap, which serves as a strong catalyst for vulcanization reaction, accelerating sulfur cross-linking and increasing network density.
[0021] Cobalt boroacylate is used to promote chemical bonding with the steel wire and ensure adhesion to the steel wire. The added resorcinol (phenolic substance) reacts with other ingredients to form a high-adhesive structure. A high amount of insoluble sulfur is used to ensure a bridge with the copper-plated surface of the steel wire. It is an ingredient that achieves an effective connection between the transition layer and the carcass cord layer.
[0022] Optionally, the antioxidant is selected from one or more of antioxidant 6PPD, antioxidant DTPD and antioxidant 4010NA, and its function is to capture free radicals in the rubber and inhibit oxidation reactions to delay the aging process of the rubber, thereby improving the rubber's resistance to heat and oxygen aging and ozone resistance.
[0023] Optionally, the stearic acid has an iodine value of ≤8.0g / 100g, an acid value of 196-211mg / g, a freezing point of 52-60°C, a saponification index of 197-212mgKOH / g, and a C 18 and C 16 The sum of the contents is ≥88wt%; its function is to react with zinc oxide in rubber to form zinc soap, thereby promoting the vulcanization reaction.
[0024] Optionally, the adhesive is selected from one or both of adhesives RA65 and HMT.
[0025] Optionally, the insoluble sulfur is selected from OT20.
[0026] Optionally, the accelerator is selected from one or more of accelerator DZ, accelerator NS and accelerator CZ.
[0027] The chemical formula of zinc methacrylate is as follows: .
[0028] The mechanism of action of zinc methacrylate with epoxy natural rubber includes three aspects: polymerization reinforcement, coordination, and interfacial interaction: (1) During rubber vulcanization, its double bonds self-polymerize to form a poly(zinc methacrylate) phase that reinforces the rubber matrix; (2) The zinc ions in poly(zinc methacrylate) coordinate with the oxygen atoms of epoxy natural rubber, increasing the crosslinking density and physical properties; (3) The polarity of epoxy natural rubber and the reactivity of the epoxy group cause it to have a strong interfacial interaction with zinc methacrylate; the polymerization of zinc methacrylate during vulcanization can also improve its own dispersion in the rubber matrix, thereby improving the material properties. This is different from the mechanism of action of other rubbers: in non-polar rubbers, zinc methacrylate is initiated by peroxide, causing the rubber matrix to crosslink and self-polymerize, forming an ionic bond crosslinking network through graft polymerization, and poly(zinc methacrylate) will also separate into nanoparticles to play a reinforcing role; for polar rubbers such as hydrogenated nitrile rubber and brominated butyl rubber, the two have good compatibility. In addition to crosslinking, they can also improve tear strength and high-temperature performance. In contrast, the coordination between zinc ions and epoxy groups and the strong interfacial interaction are the unique features of zinc methacrylate acting on epoxy natural rubber. Based on the above principle, the interfacial crosslinking and adhesion between the transition layer and the airtight layer are simultaneously enhanced.
[0029] One or more embodiments of the present invention provide a method for preparing the rubber for the tire transition layer, comprising the following steps: S1, mixing natural rubber and epoxidized natural rubber, kneading at 135-165°C to obtain a rubber section M1, and cooling; S2, mixing the first stage rubber M1, white carbon black, carbon black, silane coupling agent, zinc oxide, antioxidant and stearic acid, kneading at 142-158°C to obtain the second stage rubber M2, and cooling; S3, mixing the second stage rubber M2, cobalt boroacylate and resorcinol, kneading at 135-145°C to obtain the third stage rubber M3, and cooling; S4, mixing the three-stage glue M3 and the adhesive, kneading at 105-115°C to obtain the four-stage glue M4, and cooling; S5. Mix the fourth-stage rubber M4, zinc methacrylate, insoluble sulfur and an accelerator, and knead them at 95-105° C. to obtain the rubber for the tire transition layer.
[0030] Optionally, in S1 to S4, the cooling method includes: cooling the tablets for 8 hours.
[0031] Optionally, in S1, the internal mixer speed is 40-50 rpm, and the upper ejector pressure is 0.55-0.60 MPa.
[0032] Optionally, in S2, the internal mixer speed is 20-50 rpm, and the upper ejector pressure is 0.55-0.60 MPa.
[0033] Optionally, in S3, the internal mixer speed is 35-40 rpm, and the upper ejector pressure is 0.55-0.60 MPa.
[0034] Optionally, in S4, the internal mixer speed is 16~22rpm, and the upper ejector pressure is 0.45~0.50Mpa.
[0035] Optionally, in S5, the internal mixer speed is 15-25 rpm, and the upper ejector pressure is 0.45-0.50 MPa.
[0036] One or more embodiments of the present invention provide applications of the above-mentioned rubber for tire transition layers, including: use for bonding an airtight layer and a carcass ply.
[0037] Optionally, the airtight layer comprises brominated butyl rubber, and the carcass ply comprises natural rubber.
[0038] Example 1 A rubber for a tire transition layer comprises the following components in parts by mass: 70 parts of natural rubber, 30 parts of epoxidized natural rubber, 15 parts of carbon black, 35 parts of white carbon black, 3.5 parts of a silane coupling agent, 8 parts of zinc oxide, 2.5 parts of an antioxidant, 0.8 parts of cobalt boroacylate, 1 part of stearic acid, 1.2 parts of resorcinol, 3.5 parts of zinc methacrylate, 4 parts of an adhesive, 5 parts of insoluble sulfur, and 2 parts of an accelerator.
[0039] Among them, natural rubber STR20 acetone extract is 1.5-3.2%.
[0040] The epoxidized natural rubber was selected as ENR10 with an epoxidation degree of 10%.
[0041] The carbon black selected was carbon black N326.
[0042] Silica content of white carbon black ≥92.0%, heating loss (105℃) 5.5±1.5, ignition loss ≤6.0, specific surface area 165±15m 2 / g.
[0043] The silane coupling agent selected is Si-69, wherein the sulfur content is 22.5±0.8%, the S2 content is 17.5±2.0%, the S3 content is 30.0±2.0%, the S4 content is 20.5±2.0%, the S5~S8 content is 24.5±2.0%, and the average polysulfide bond length is 3.30±0.1.
[0044] Zinc oxide is indirect zinc oxide, with a zinc oxide content of ≥99.50% and a specific surface area of 8.0±1.0m 2 / g.
[0045] The antioxidant is 6PPD, wherein the content of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine is ≥96.0wt%.
[0046] The cobalt content in cobalt boroacylate is 22.5±0.7wt%.
[0047] Stearic acid, iodine value ≤8.0g / 100g, acid value 196-211mg / g, freezing point 52-60℃, saponification index 197-212mgKOH / g, C18+C16 content ≥88%.
[0048] The DSC melting point of resorcinol is 110.0~114.0℃.
[0049] The adhesive was selected as RA65, with acetone insoluble matter of 34.0±2.5wt% and ash (850℃) of 30-35wt%.
[0050] The insoluble sulfur was selected as OT20, with an oil content of 19.5±1.5%, a total sulfur content of 80.0±1.5%, a thermal reduction of ≤25%, and a DSC melting point of 132.0±6.0°C.
[0051] The accelerator is accelerator DZ, with a sulfenamide component (excluding oil) ≥ 97% and a cyclohexane insoluble matter ≤ 0.5%.
[0052] The active ingredient content of zinc methacrylate is ≥98.0wt%, the moisture content is ≤2.0wt%, the pH value is 5-7, the ZnO content is 35-38wt%, the ash content is ≤38wt%, and the specific surface area is 30-35m 2 / g.
[0053] The preparation method comprises: S1. Use a GK420 internal mixer to produce a first-stage rubber M1. Set the internal mixer speed to 50 rpm, the upper push pin pressure to 0.55 MPa, and the mixing chamber water temperature to 35±5°C. Add the natural rubber and epoxidized natural rubber mixture into the internal mixer, press the upper push pin until the pressure reaches the set value and hold for 40 seconds; then lift the upper push pin and hold for 5 seconds; then press the upper push pin and hold it until the rubber temperature reaches 135°C, then lift the upper push pin; then press the upper push pin and hold it until the rubber temperature reaches 165°C, empty the rubber in the internal mixer into a twin-screw extruder (parameter setting: the distance between the two rollers is set to 8 cm to 15 cm, the roller temperature is 100±5°C, and the screw temperature is 95±10°C). The first-stage rubber M1 is pressed into sheets and cooled and parked for 8 hours for use.
[0054] S2. Use internal mixer GK420 to make second stage rubber M2, set internal mixer speed to 48rpm, upper push pin pressure to 0.55Mpa, and control mixing chamber water temperature at 35±5℃; add first stage rubber M1 into internal mixer, press down upper push pin until pressure reaches set value and hold for 20s; then lift up upper push pin, add white carbon black, carbon black N326, silane coupling agent, zinc oxide, antioxidant, and stearic acid; then press down upper push pin and hold for 30s, at this time adjust internal mixer speed to 35rpm, then lift up Lift the top plug and add the antioxidant and hold it for 5 seconds; then press the top plug and hold it until the rubber temperature reaches 142℃, at this time adjust the speed of the internal mixer to 20rpm; then lift the top plug and hold it for 60s; then press the top plug and hold it until the rubber temperature reaches 158℃, empty the rubber in the internal mixer into a twin-screw extruder (parameter setting: the distance between the two rollers is set to 5cm~8cm, the roller temperature is 95±5℃, and the screw temperature is 85±10℃), and cool the second-stage rubber M2 tablets for 8 hours for standby use.
[0055] S3. Use internal mixer GK420 to make three-stage rubber M3, set the internal mixer speed to 35rpm, the upper push pin pressure to 0.55Mpa, and the mixing chamber water temperature to 35±5℃; add the second-stage rubber M2, cobalt borylate and resorcinol into the internal mixer, press down the upper push pin and hold it until the pressure reaches the set value for 40s; then lift the upper push pin and hold it for 5s; then press down the upper push pin and hold it for 40s, then lift the upper push pin and hold it for 5s; then press down the upper push pin and hold it until the rubber temperature reaches 145℃, empty the rubber in the internal mixer into a twin-screw extruder (parameter setting: the distance between the two rollers is set to 5cm~10cm, the roller temperature is 95±10℃, and the screw temperature is 85±10℃), and cool the three-stage rubber M3 for tableting for 8 hours for standby use.
[0056] S4. Use internal mixer GK255 to make four-stage rubber M4, set the internal mixer speed to 22rpm, the upper push pin pressure to 0.45Mpa, and the mixing chamber water temperature to 30±5℃; add three-stage rubber M3 and adhesive into the internal mixer, press down the upper push pin and hold it until the pressure reaches the set value for 35s; then lift the upper push pin and hold it for 5s; then press down the upper push pin and hold it for 25s, then lift the upper push pin and hold it for 5s; then press down the upper push pin and hold it until the rubber temperature reaches 115℃, empty the rubber in the internal mixer into the open mixer, and press the rubber into sheets (parameter setting: the distance between the two rollers is set to 5cm~10cm, and the roller temperature is <70℃). Cool the four-stage rubber M4 sheets for 8 hours for standby use.
[0057] S5. Use GK255 internal mixer to make the final rubber mix. Set the internal mixer speed to 22 rpm, the upper push pin pressure to 0.45 MPa, and the mixing chamber water temperature to 30±5°C. Add the fourth-stage rubber M4, zinc methacrylate, insoluble sulfur, and accelerator to the internal mixer. Press the upper push pin until the pressure reaches the set value and hold it for 30 seconds. Then lift the upper push pin and hold it for 5 seconds. Then press the upper push pin and hold it for 20 seconds. At this time, adjust the internal mixer speed to 16 rpm, then lift the upper push pin and hold it for 5 seconds. Then press the upper push pin and hold it until the rubber temperature reaches 105°C. Empty the rubber in the internal mixer into the open mixer for sheeting (parameter setting: the distance between the two rollers is set to 5 cm to 10 cm, and the roller temperature is <70°C). Press the final rubber mix into sheets for subsequent tread production.
[0058] Example 2 A rubber for a tire transition layer comprises the following components in parts by mass: 50 parts of natural rubber, 50 parts of epoxidized natural rubber, 18 parts of carbon black, 42 parts of white carbon black, 4.2 parts of a silane coupling agent, 10 parts of zinc oxide, 3.5 parts of an antioxidant, 1.2 parts of cobalt boroacylate, 1.5 parts of stearic acid, 2 parts of resorcinol, 10 parts of zinc methacrylate, 5 parts of an adhesive, 6 parts of insoluble sulfur, and 2.5 parts of an accelerator. The epoxidized natural rubber is ENR50 with an epoxidation degree of 50%.
[0059] The difference from Example 1 is that each material component is at the upper threshold value of the range of the example.
[0060] The specifications and preparation methods of the raw materials are the same as those in Example 1.
[0061] Example 3 A rubber for a tire transition layer comprises the following components in parts by mass: 90 parts of natural rubber, 10 parts of epoxidized natural rubber, 13.5 parts of carbon black, 31.5 parts of white carbon black, 3.15 parts of a silane coupling agent, 5 parts of zinc oxide, 1.5 parts of an antioxidant, 0.3 parts of cobalt boroacylate, 0.5 parts of stearic acid, 0.5 parts of resorcinol, 2 parts of zinc methacrylate, 3 parts of an adhesive, 4.5 parts of insoluble sulfur, and 1.3 parts of an accelerator.
[0062] The difference from Example 1 is that each material component is at the lower threshold value of the range of the embodiment.
[0063] The specifications and preparation methods of the raw materials are the same as those in Example 1.
[0064] Comparative Example 1 A rubber for a tire transition layer, comprising the following components in parts by mass: 100 parts of natural rubber, 50 parts of carbon black, 10 parts of white carbon black, 8 parts of zinc oxide, 2 parts of an antioxidant, 1 part of cobalt boroacylate, 0.5 parts of stearic acid, 1 part of resorcinol, 3 parts of an adhesive, 5 parts of insoluble sulfur, and 1.4 parts of an accelerator; The main differences from Example 1 are that epoxy natural rubber, silane coupling agent and zinc methacrylate are not added, and the amount of carbon black added is increased while the amount of white carbon black added is reduced.
[0065] The specifications of the raw materials are the same as those in Example 1.
[0066] The preparation method is adjusted appropriately according to the raw materials, including: S1. Use GK420 internal mixer to make a rubber M1. Set the internal mixer speed to 48rpm, the upper bolt pressure to 0.55Mpa, and the water temperature in the mixing chamber to 35±5℃. Add natural rubber to the internal mixer, press the upper bolt until the pressure reaches the set value and hold it for 20s; then lift the upper bolt, add white carbon black, carbon black N326, zinc oxide, antioxidant, and stearic acid; then press the upper bolt and hold it for 30s. At this time, adjust the internal mixer speed to 35rpm, and then lift the upper bolt. Add the antioxidant and hold it for 5 seconds; then press down the top bolt and hold it until the temperature of the rubber compound reaches 142°C. At this time, the speed of the internal mixer is adjusted to 20 rpm; then lift the top bolt and hold it for 60 seconds; then press down the top bolt and hold it until the temperature of the rubber compound reaches 158°C, and then empty the rubber compound in the internal mixer into a twin-screw extruder (parameter setting: the distance between the two rollers is set to 5cm~8cm, the roller temperature is 95±5°C, and the screw temperature is 85±10°C). Press a section of rubber M1 into a sheet and cool it for 8 hours for use.
[0067] S2. Use internal mixer GK420 to make second-stage rubber M2, set the internal mixer speed to 35rpm, the upper push pin pressure to 0.55Mpa, and the mixing chamber water temperature to 35±5℃; add first-stage rubber M1, cobalt boroacylate and resorcinol into the internal mixer, press down the upper push pin and hold it until the pressure reaches the set value for 40s; then lift the upper push pin and hold it for 5s; then press down the upper push pin and hold it for 40s, then lift the upper push pin and hold it for 5s; then press down the upper push pin and hold it until the rubber temperature reaches 145℃, empty the rubber in the internal mixer into a twin-screw extruder (parameter setting: the distance between the two rollers is set to 5cm~10cm, the roller temperature is 95±10℃, and the screw temperature is 85±10℃), and cool the second-stage rubber M2 for tableting for 8 hours for standby use.
[0068] S3. Use internal mixer GK255 to make three-stage rubber M3, set the internal mixer speed to 22rpm, the upper push pin pressure to 0.45Mpa, and the mixing chamber water temperature to 30±5℃; add the second-stage rubber M2 and adhesive into the internal mixer, press down the upper push pin and hold it until the pressure reaches the set value for 35s; then lift the upper push pin and hold it for 5s; then press down the upper push pin and hold it for 25s, then lift the upper push pin and hold it for 5s; then press down the upper push pin and hold it until the rubber temperature reaches 115℃, empty the rubber in the internal mixer into the open mixer, and press the rubber into sheets (parameter setting: the distance between the two rollers is set to 5cm~10cm, and the roller temperature is <70℃). Cool the three-stage rubber M3 for sheeting for 8 hours for standby use.
[0069] S4. Use internal mixer GK255 to make final rubber mix, set internal mixer speed to 22rpm, upper push pin pressure to 0.45Mpa, and mixing chamber water temperature to 30±5℃; add three-stage rubber M3, insoluble sulfur and accelerator into internal mixer, press down the upper push pin until the pressure reaches the set value and hold for 30s; then lift the upper push pin and hold for 5s; then press the upper push pin and hold for 20s. At this time, adjust the internal mixer speed to 16rpm, then lift the upper push pin and hold for 5s; then press the upper push pin and hold until the rubber temperature reaches 105℃, empty the rubber in the internal mixer into the open mixer, and press the final rubber mix into sheets (parameter setting: the distance between the two rollers is set to 5cm~10cm, and the roller temperature is <70℃). Press the final rubber mix into sheets for subsequent tread production.
[0070] Comparative Example 2 A rubber for a tire transition layer, comprising the following components in parts by mass: 70 parts of natural rubber, 30 parts of epoxidized natural rubber, 50 parts of carbon black, 10 parts of white carbon black, 8 parts of zinc oxide, 2 parts of an antioxidant, 1 part of cobalt boroacylate, 0.5 parts of stearic acid, 1 part of resorcinol, 3 parts of an adhesive, 5 parts of insoluble sulfur, and 1.4 parts of an accelerator; The difference from Comparative Example 1 is that 30 parts of the natural rubber are replaced by epoxidized natural rubber.
[0071] Other raw materials are the same as those in Example 1.
[0072] The preparation method is adjusted appropriately according to the raw materials, including: S1. This step is the same as step S1 in Example 1. A piece of glue is obtained at the end of the step.
[0073] S2. This step is the same as step S1 of comparative example 1, except that the first-stage rubber of this comparative example is used to replace the natural rubber of comparative example 1, and the second-stage rubber is obtained after the step is completed.
[0074] S3. This step is the same as step S2 of comparative example 1, except that the second-stage adhesive of this comparative example is used to replace the first-stage adhesive of comparative example 1, and a third-stage adhesive is obtained after the step is completed.
[0075] S4. This step is the same as step S3 of comparative example 1, except that the three-stage adhesive of this comparative example is used instead of the two-stage adhesive of comparative example 1, and four-stage adhesive is obtained after the step is completed.
[0076] S5. This step is the same as step S4 of comparative example 1, except that the four-stage rubber of this comparative example is used instead of the three-stage rubber of comparative example 1. After the step is completed, the final rubber mixture is obtained.
[0077] Comparative Example 3 A rubber for a tire transition layer, comprising the following components in parts by mass: 70 parts of natural rubber, 30 parts of epoxidized natural rubber, 50 parts of carbon black, 10 parts of white carbon black, 8 parts of zinc oxide, 2 parts of an antioxidant, 1 part of cobalt boroacylate, 0.5 parts of stearic acid, 1 part of resorcinol, 3.5 parts of zinc methacrylate, 3 parts of an adhesive, 5 parts of insoluble sulfur, and 1.4 parts of an accelerator; The difference from Comparative Example 1 is that 30 parts of the natural rubber are replaced by epoxy natural rubber, and zinc methacrylate is added.
[0078] Other raw material requirements are the same as in Example 1.
[0079] The preparation method is adjusted appropriately according to the raw materials, including: S1. This step is the same as step S1 in Example 1. A piece of glue is obtained at the end of the step.
[0080] S2. This step is the same as step S1 of comparative example 1, except that the first-stage rubber of this comparative example is used to replace the natural rubber of comparative example 1, and the second-stage rubber is obtained after the step is completed.
[0081] S3. This step is the same as step S2 of comparative example 1, except that the second-stage adhesive of this comparative example is used to replace the first-stage adhesive of comparative example 1, and a third-stage adhesive is obtained after the step is completed.
[0082] S4. This step is the same as step S3 of comparative example 1, except that the three-stage adhesive of this comparative example is used instead of the two-stage adhesive of comparative example 1, and four-stage adhesive is obtained after the step is completed.
[0083] S5. This step is the same as step S4 of comparative example 1, except that the four-stage rubber of this comparative example is used instead of the three-stage rubber of comparative example 1, and zinc methacrylate is added. After the step is completed, the final rubber mixture is obtained.
[0084] Preparation Example 1 This preparation example provides an airtight layer rubber, which is used to test the adhesive properties of the rubber for the tire transition layer provided in various embodiments and comparative examples.
[0085] The airtight layer rubber includes the following components in parts by mass: 100 parts of bromobutyl rubber, 65 parts of carbon black, 4 parts of zinc oxide, 2 parts of stearic acid, 0.5 parts of insoluble sulfur, 2 parts of accelerator, 8 parts of hydrocarbon resin mixed resin, 0.6 parts of magnesium oxide and 7 parts of naphthenic oil.
[0086] Among them, the carbon black is selected as carbon black N660.
[0087] Performance testing Performance testing includes: adhesion testing, tensile performance testing and wire pull-out force testing before aging and after 96h*80℃ aging.
[0088] The adhesion testing method includes the following steps.
[0089] (1) Sample preparation: Two pieces of steel cord fabric with a width of 25 mm and a length of 25 cm are selected as the skeleton material, and the tire transition layer rubber film obtained in each embodiment or comparative example and the airtight layer film obtained in Preparation Example 1 are uniformly wrapped on the surface of the two pieces of steel cord fabric respectively with a thickness of 1 mm; the two wrapped pieces of steel cord fabric are laminated together, and a piece of cellophane with a length of 5 cm and a width of 10 cm is placed at the laminating interface from one end of the cord fabric toward the center of the area to form the sample; the cellophane is used to ensure that after vulcanization, a 5 cm isolation zone is formed at one end of the sample and a 20 cm bonding zone is formed at the other end; wherein, the tire transition layer rubber film material is selected from one of the above embodiments and comparative examples, and the airtight layer film material is selected from the material prepared in Preparation Example 1.
[0090] (2) Vulcanization treatment: Place the prepared sample in a flat vulcanizer for vulcanization, set the vulcanization pressure to 8~10 bar, and the vulcanization condition to keep warm at 150℃ for 60 minutes; after vulcanization, let the sample stand for 8 hours to fully release the internal stress and stabilize the performance, and obtain the test sample.
[0091] (3) Performance test: The two steel cord films separated by cellophane of the test sample before or after aging were respectively mounted on the upper and lower clamps of the high-speed rail strength tester (model AI-7000S). The stretching speed was set to 50 mm / min, and the equipment was started. The upper clamp was stretched upward to a position of 10 cm. The average force value during the stretching process was recorded. The force value was the interlayer bonding strength between the transition layer and the airtight layer.
[0092] The tensile properties test is carried out in accordance with GB / T528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”.
[0093] The steel wire pull-out force test is carried out in accordance with GB / T3513-2018 "Determination of the adhesion between vulcanized rubber and single steel wire - Extraction method".
[0094] The test results are shown in Table 1.
[0095] Table 1
[0096] Among them, the measured value of the interlayer adhesion of Comparative Example 1 before aging is 120N, and the measured value of the interlayer adhesion of Example 1 is 193, which is increased to 161% of Comparative Example 1; the measured value of the interlayer adhesion of Comparative Example 1 after aging is 80N, and the measured value of the interlayer adhesion of Example 1 is 156, which is increased to 158% of Comparative Example 1. The interlayer adhesion is directly related to the delamination problem of the tire. Therefore, the solution of the present invention can effectively solve the delamination problem and improve the overall performance and safety reliability of the tire.
[0097] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A rubber for a tire transition layer, characterized in that it comprises The following components are included in parts by mass: 50-90 parts of natural rubber, 50-10 parts of epoxidized natural rubber, 13.5-18 parts of carbon black, 31.5-42 parts of white carbon black, 3.15-4.2 parts of silane coupling agent, 5-10 parts of zinc oxide, 1.5-3.5 parts of antioxidant, 0.3-1.2 parts of cobalt boroacylate, 0.5-1.5 parts of stearic acid, 0.5-2 parts of resorcinol, 2-10 parts of zinc methacrylate, 3-5 parts of adhesive, 4.5-6 parts of insoluble sulfur and 1.3-2.5 parts of accelerator; wherein the sum of the natural rubber and epoxidized natural rubber components is equal to 100 parts, and the mass ratio of white carbon black to carbon black is (6-8):(2-4).
2. The tire transition layer rubber according to claim 1, wherein: The natural rubber grade is STR20; or the epoxidized natural rubber has an epoxidation degree of 10% to 20%, preferably ENR10 with an epoxidation degree of 10%.
3. The tire transition layer rubber according to claim 1, wherein: The carbon black is selected from one or more of N326, N375 and N330; Or, the specific surface area of the white carbon black is 165±15m 2 / g; or, the silane coupling agent is selected from one or two of Si-69 and Si-75.
4. The tire transition layer rubber according to claim 1, wherein: The specific surface area of zinc oxide is 8.0±1.0m 2 / g; Or, the antioxidant is selected from one or more of antioxidant 6PPD, antioxidant DTPD and antioxidant 4010NA; Or, the stearic acid has an iodine value of ≤8.0g / 100g, an acid value of 196-211mg / g, a freezing point of 52-60°C, a saponification index of 197-212mgKOH / g, and a C 18 and C 16 The sum of the contents is ≥88wt%.
5. The tire transition layer rubber according to claim 1, wherein: The adhesive is selected from one or two of adhesives RA65 and HMT; Or, the insoluble sulfur is selected as OT20; Alternatively, the accelerator is selected from one or more of accelerator DZ, accelerator NS and accelerator CZ.
6. A method for preparing the rubber for a tire transition layer according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, mixing natural rubber and epoxidized natural rubber, kneading at 135-165°C to obtain a rubber section M1, and cooling; S2, mixing the first stage rubber M1, white carbon black, carbon black, silane coupling agent, zinc oxide, antioxidant and stearic acid, kneading at 142-158°C to obtain the second stage rubber M2, and cooling; S3, mixing the second stage rubber M2, cobalt boroacylate and resorcinol, kneading at 135-145°C to obtain the third stage rubber M3, and cooling; S4, mixing the three-stage glue M3 and the adhesive, kneading at 105-115°C to obtain the four-stage glue M4, and cooling; S5. Mix the fourth-stage rubber M4, zinc methacrylate, insoluble sulfur and an accelerator, and knead them at 95-105° C. to obtain the rubber for the tire transition layer.
7. The method for preparing the rubber for the tire transition layer according to claim 6, wherein: In S1 to S4, the cooling method includes: cooling the tablets for 8 hours.
8. The method for preparing the rubber for the tire transition layer according to claim 6, wherein: In S1, the internal mixer speed is 40~50rpm, and the upper ejector pressure is 0.55~0.60Mpa; Alternatively, in S2, the internal mixer speed is 20-50 rpm, and the upper ejector pressure is 0.55-0.60 MPa; Alternatively, in S3, the internal mixer speed is 35-40 rpm, and the upper ejector pressure is 0.55-0.60 MPa; Alternatively, in S4, the internal mixer speed is 16-22 rpm, and the upper ejector pressure is 0.45-0.50 MPa; Alternatively, in S5, the internal mixer speed is 15-25 rpm, and the upper ejector pressure is 0.45-0.50 MPa.
9. An application of the rubber for a tire transition layer according to any one of claims 1 to 5, characterized in that: Used to bond the inner liner and carcass ply.
10. The use of the rubber for tire transition layer according to claim 9, characterized in that: The inner liner comprises bromobutyl rubber, and the carcass ply comprises natural rubber.
Citation Information
Patent Citations
Special oil-resistant aging-resistant natural rubber cable material for oil wells
CN104629102A
Oil-resistant aging-resistant natural rubber cable material
CN106397852A
Epoxidized natural rubber composite material and preparation method thereof
CN107501663A
Tire transition layer rubber as well as preparation method and application thereof
CN118755155A
Rubber composition for tire tread and pneumatic tire using the same
EP1577341A1